1983
DOI: 10.1152/ajpregu.1983.245.3.r433
|View full text |Cite
|
Sign up to set email alerts
|

Differential pattern of sympathetic outflow during upper airway stimulation with smoke

Abstract: This study investigates directly the possibility that sympathetic discharge to the heart is decreased while it is increased to other organs during upper respiratory perfusion with cigarette smoke. Blood pressure (BP), heart rate, ECG, and respiratory movements were monitored in urethane-anesthetized rabbits. Insertion of two cannulas allowed respiration of room air while passing smoke across the upper respiratory irritant receptors and out through the nares. Through a retroplural incision, the left stellate ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…This baroreceptor-independent reflex is produced by stimulating trigeminal afferents with an irritant, usually smoke, which produces a large increase in renal SNA [58]. We have shown that this method of normalization eliminated the 50% decay in SNA that occurred over the 5-week course of the experiments [49].…”
Section: Percentage Of Nasopharyngeal Sna Maximummentioning
confidence: 84%
See 1 more Smart Citation
“…This baroreceptor-independent reflex is produced by stimulating trigeminal afferents with an irritant, usually smoke, which produces a large increase in renal SNA [58]. We have shown that this method of normalization eliminated the 50% decay in SNA that occurred over the 5-week course of the experiments [49].…”
Section: Percentage Of Nasopharyngeal Sna Maximummentioning
confidence: 84%
“…The baroreflex inhibition was not detectable when SNA was calibrated using other methods, such as resting SNA, the upper plateau of the baroreflex curve, or airjet stress [49]. The advantage of this approach is that it is an independent standard that can be used in both conscious and anesthetized rabbits [58]. Using the nasopharyngeal reflex for normalization, we and others have shown that renal SNA is not elevated in angiotensin II-treated rabbits and in rabbits Fig.…”
Section: Percentage Of Nasopharyngeal Sna Maximummentioning
confidence: 86%
“…This is reflected in the diverse response patterns of subsets of these neurones to various afferent inputs. For example, during the defence reaction there is an increase in sympathetic drive to the heart, and renal and mesenteric vascular beds, but a withdrawal of sympathetic drive to limb muscle vasculature (Yardley & Hilton, 1986); stimulation of upper airway irritant receptors with smoke results in a withdrawal of sympathetic drive to the heart and an increase in renal sympathetic nerve activity (Peterson, Coote, Gilbey & Futuro-Neto, 1983). Subsets of sympathetic preganglionic neurones respond differently to, for example, certain somatic stimuli and chemoreceptor stimulation (Jiinig & Szulczyk, 1980;Gilbey & Stein, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, responses similar to those seen during underwater submersion of marine mammals can be elicited in smaller laboratory mammals. For example, stimulation of the nasal mucosa of laboratory mammals with irritant vapors (15,26,32,57,60,71,73,74,76,79,81,99,100,103) also elicits dramatic changes in cardiorespiratory function similar to those seen in aquatic mammals with submersion. This feature is advantageous since various pharmacological and physiological tests can be done on table preparations in a more controlled laboratory setting.…”
mentioning
confidence: 99%